1975
DOI: 10.1042/bj1480139
|View full text |Cite
|
Sign up to set email alerts
|

The breakdown of lipid reserves in the endosperm of germinating castor beans

Abstract: 1. Lipid extracts were obtained from castor-bean endosperm tissue at various times during germination and, after purification, the total lipid content was determined. Quantitative measurements of the triglyceride and phospholipid content together with the fatty acid composition were made. 2. The total lipid content of the endosperm rapidly decreased during germination; after 10 days less than 20% of the original weight of lipid remained. In contrast, the phospholipid content (initially less than 0.5 % of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
1

Year Published

1977
1977
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 37 publications
1
21
1
1
Order By: Relevance
“…The newly synthesized diglycerides contain no ricinoleate (6). However, this activity does not -significantly alter the composition of the storage lipid (11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The newly synthesized diglycerides contain no ricinoleate (6). However, this activity does not -significantly alter the composition of the storage lipid (11).…”
Section: Discussionmentioning
confidence: 99%
“…After 6 days germination when most of the storage lipid has been degraded (11,13) several new lipid classes become apparent ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that accumulation of these three enzymes was dependent on GA action. Marriott and Northcote (1975) showed that GAs stimulate the induction of isocitrate lyase activity during germination. Moreover, a TAACAAA sequence analogous to the GARE is present in position Ϫ1403 and Ϫ233 of the genes encoding isocitrate lyase and phosphoglyceromutase, respectively.…”
Section: Mobilization Of Stored Lipid Seed Reservesmentioning
confidence: 99%